Challenging a Misnomer? The Role of Inflammatory Pathways in Inflammatory Breast Cancer - Riley J. Morrow; Nima Etemadi; Belinda Yeo; Matthias Ernst (Mediators of Inflammation)
Inflammatory breast cancer is a rare, yet highly aggressive form of breast cancer, which accounts for less than 5% of all locally advanced presentations. The clinical presentation of inflammatory breast cancer often differs significantly from that of noninflammatory breast cancer; however, immunohistochemistry reveals few, if any, distinguishing features. The more aggressive triple-negative and HER2-positive breast cancer subtypes are overrepresented in inflammatory breast cancer compared with noninflammatory breast cancer, with a poorer prognosis in response to conventional therapies. Despite its name, there remains some controversy regarding the role of inflammation in inflammatory breast cancer. This review summarises the current molecular evidence suggesting that inflammatory signaling pathways are upregulated in this disease, including NF-κB activation and excessive IL-6 production among others, which may provide an avenue for novel therapeutics. The role of the tumor microenvironment, through tumor-associated macrophages, infiltrating lymphocytes, and cancer stem cells is also discussed, suggesting that these tumor extrinsic factors may help account for the differences in behavior between inflammatory breast cancer and noninflammatory breast cancer. While there are various novel treatment strategies already underway in clinical trials, the need for further development of preclinical models of this rare but aggressive disease is paramount.